The influence of the video assistance referee (VAR) on the English Premier League - Bao, R.; Han, B. (International Journal of Performance Analysis in Sport, 2024)
The Video Assistant Referee (VAR) was introduced into football in order to assist referees in their decision making during the match. The English Premier League (EPL) introduced VAR in the 2019-2020 season. The aim of this study was to explore the influence of the introduction of VAR on the English Premier League. The sample includes all 380 matches played in the 2018-2019 season without VAR and all 380 matches played in the 2019-2020 season with VAR. The following nine variables were collected for each match: the first half time, the second half time, total time, goals, penalties, fouls, yellow cards, red cards and offsides. These variables were compared pre and post the introduction of VAR using means comparison and Mixed Linear Model (MLM). The results demonstrated that after the introduction of VAR, the first half time, second half time, total time and fouls increased significantly (p< 0.01). In contrast, a significant decrease (p< 0.01) was found in the number of offsides after the implementation of VAR. The findings may help football practitioners and fans better understand the impact of VAR on European top professional football leagues, particularly on the English Premier League and also help to optimise referees` officiating strategies.